The Indonesian Version of the Exercise Self-Efficacy Scale: Cross-cultural Adaptation and Psychometric Testing - Arif R. Hakim; Shan-Tair Wang; Fransiskus X. Widiantoro; Mujib Hannan; Chi-Jane Wang; Suzan J. Fetzer (Elsevier, 2020)
Summary: Purposes: The study aimed to translate the Exercise Self-Efficacy Scale (ESES) into Indonesian and test the cultural equivalence, reliability, and validity of the new version for university students. Methods: The cross-sectional study recruited 379 Indonesian university students using convenience sampling. Phase 1, a culturally appropriate version of the ESES was developed in the Indonesian language. Phase 2, the psychometric properties were determined through exploratory factor analysis, bootstrap factor analysis, and confirmatory factor analysis. The internal consistency reliability was tested using Cronbach's α, whereas the stability using intraclass correlation coefficient to assess. Results: The students' ages ranged from 17 to 39 years, and 65.0% were women. For translation equivalence, the mean item content validity indexes ranged from 3.5 to 4, and all items were understandable. The 16-item scale exhibited cross-cultural appropriateness and readability, with a three-factor model explaining 62.3% of the variance in exercise self-efficacy. A bootstrap analysis using 100 resamples further confirmed the three-factor model. The indices of the good-fit model that used the three-factor by two-stage least squares method were satisfactory, with χ2/df = 3.3, goodness of fit index = .88, and root mean-square error of approximation = .05 (p < .001). The Cronbach's α was .78, .80, and .92 for factors 1, 2, and 3, respectively. The test--retest reliability was demonstrated with an intraclass correlation coefficient of .91, indicating adequate measurement stability. Conclusion: The 16-item ESES-I has acceptable validity and reliability; however, a broader application of the scale requires further testing in different populations to confirm its external validity.